Thermal ablation of ultrasound and non-contrast computed tomography invisible primary and secondary liver tumors: targeting by selective intra-arterial lipiodol injection - Adrian Kobe; Lambros Tselikas; Frédéric Deschamps; Charles Roux; Alexandre Delpla; Eloi Varin; Antoine Hakime; Thierry de Baère (Diagnostic and Interventional Radiology, 2023)

(untitled)
PURPOSETo evaluate the technical feasibility and outcomes of thermal ablation following selective intra-arterial lipiodol injection (SIALI) for targeting primary and secondary liver tumors invisible on ultrasound (US) and non-contrast computed tomography (CT).METHODSThis retrospective study included 18 patients with 20 tumors (67% male, mean age 60.8 ± 12.1 years). The 20 tumors included 15 liver metastases and 5 hepatocellular carcinomas. All patients underwent single-session SIALI and subsequent CT-guided thermal ablation. The primary outcome was a technical success, defined as visualization of the tumor after SIALI and successful thermal ablation. Secondary outcomes were local recurrence rate and procedure-related complications.RESULTSThe median tumor size was 1.5 (1–2.5) cm. In addition, SIALI was performed with a median volume of 3 (1–10) mL of lipiodol resulting in intra-tumoral iodized oil accumulation in 19 tumors and negative imprint with iodized oil accumulation of the surrounding liver parenchyma in 1 tumor. The technical success rate was 100%. No local occurrence was observed at a mean follow-up time of 3 ± 2.5 years.CONCLUSIONSIALI to tag liver tumors not visible with US and non-contrast CT before percutaneous ablation is highly feasible and has a high success rate for the treatment of both primary and secondary liver tumors.